STRING v11: protein-protein association networks with increased coverage, supporting functional discovery in genome-wide experimental datasets - Szklarczyk, Damian; Bork, Peer (Nucleic acids research, 2019)
Abstract. Proteins and their functional interactions form the backbone of the cellular machinery. Their connectivity network needs to be considered for the ful